Avaliação dos teores de metais pesados no solo e na planta de cana-de-açúcar sob adubação com lodo de esgoto e vinhaça - Camilotti, Fabio [UNESP]; Andrioli, Itamar; Marques, Marcos Omir; da Silva, Alysson Roberto; Tasso Junior, Luiz Carlos (Universidade Federal de Uberlândia (UFU), 2009)
The objective of this work was to evaluate Cd, Cr, Ni and Pb total contents in soil and sugar cane after four annual applications of sewage sludge and vinasse to supply all N and all K required by the crop. A field experiment was carried out on clayey Typic Haplustox. It was used a randomized block design with seven treatments and three replications. The treatments consisted in: (i) rate of sewage sludge to supply 100% of the N required by the crop; (ii) rate of sewage sludge to supply 200% of the N required; (iii) rate of vinasse to supply 100% of the K required; (iv) rate of vinasse to supply 200% of the K required; ( v) combination of the treatments ( i) and ( iii); ( vi) combination of the treatments ( ii) e ( iv); (vii) control ( mineral fertilization). The contents of Cd, Cr, Ni and Pb in sewage sludge reached maximum values of 1.58, 41.66, 35.17 and 45.25 mg kg(-1), respectively. These metals were not detected in vinasse. The residues were applied annually for four years. At the end of this period, sewage sludge and vinasse accumulated rates, that get up to 51 t ha(-1) and 762 m(3) ha(-1), respectively, did not cause alteration in Cd, Cr, Ni and Pb total contents in soil, up to 50 cm of depth, and in plant. Sewage sludge and vinasse application to supply N and K for sugar cane did not offer soil pollution risk by heavy metals.

O objetivo deste trabalho foi avaliar os teores totais de Cd, Cr, Ni e Pb no solo e na cana-de-açúcar após quatro aplicações anuais de lodo de esgoto e vinhaça em doses suficientes para fornecer todo N e todo K exigidos pela cultura. O experimento foi conduzido em Latossolo Vermelho argiloso. O delineamento experimental foi em blocos casualizados com sete tratamentos e três repetições. Os tratamentos consistiram em: (i) dose de lodo de esgoto para suprir 100% do N exigido pela cultura; (ii) dose de lodo de esgoto para suprir 200% do N exigido; (iii) dose de vinhaça para suprir 100% do K exigido; (iv) dose de vinhaça para suprir 200% do K exigido; (v) combinação dos tratamentos (i) e (iii); (vi) combinação dos tratamentos (ii) e (iv); (vii) testemunha (adubação mineral). Os teores de Cd, Cr, Ni e Pb no lodo de esgoto atingiram valores máximos de 1,58, 41,66, 35,17 e 45,25 mg kg–1, respectivamente. Esses metais não foram detectados na vinhaça. Os resíduos foram aplicados anualmente por quatro anos. Ao final desse período, as doses acumuladas de lodo de esgoto e de vinhaça, que chegaram até 51 t ha–1 e 762 m3 ha–1, respectivamente, não provocaram alteração nos teores totais de Cd, Cr, Ni e Pb no solo, até 50 cm de profundidade, e na planta. A aplicação de lodo de esgoto e vinhaça para fornecer N e K para a cana-de-açúcar não ofereceu risco de poluição do solo por metais pesados.
Evaluation of heavy metals contents in soil and sugarcane plant under fertilization with sewage sludge and vinasse
Keywords: Heavy metals; Organic residue; Pollution; soil; Sugarcane